Al-Ma'un Praxis Movement in Empowering Destitute Families by the Students - Haq, Andri Moewashi Idharoel; Muhtadi, Asep Saeful; Kahmad, Dadang; AS, Enjang (Hanifiya: Jurnal Studi Agama-Agama, 2022)
This research aims to analyze the Al-Maun Praxis movement as a new religion-based social movement in Indonesia, implicating its role and influence in educational institutions. The phenomenon of the Al-Ma'un praxis movement developed by Muhammadiyah universities has been studied scientifically by a sociological approach, especially the new social movement with its two theories; the theory of resource mobilization and identity-oriented theory. However, this research shows that those two theories can be used simultaneously by prioritizing the identity-oriented approach and then analyzing the resource mobilization theory. This research discusses the Muhammadiyah organization with the Al-Ma'un Praxis Movement Program at PTM as a model for a new religious-based social movement in Indonesia; in identity-oriented theory, Muhammadiyah as Movement Identity and Surat Al-Ma'un as Movement Theology, and Muhammadiyah as Movement Ideology. The more comprehensive areas in the idea of resource mobilization are: Islam and Mohammadness (Agama Islam dan Kemuhammadiyahan; AIK) as medium to mobilize Muhammadiyah resources, the capital of resource mobilization comes from Muhammadiyah residents at Muhammadiyah Universities, Mobilization of resources in the form of empowerment of charity and creativity based on Muhammadiyah philanthropy.